A resolution for a quiet revolution: taking the United Nations to sustainable development `beyond aid' - Pio Wennubst; Timo Mahn (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
What is the future role of the United Nations development system (UNDS), how will it function and what are the necessary means? The UNDS seems to be well positioned to play a key role in implementing the Sustainable Development Agenda. Preparations for the paradigm shift to Sustainable Development require reforms. This paper contributes to these debates by taking the Quadrennial Comprehensive Policy Review (QCPR) as a starting point. The QCPR has evolved into a key vehicle for making system-wide reforms within the UNDS. There currently is no organic link between the mandate and the operations because only fragments of a negotiated system-wide mandate exist. The paper suggests how the QCPR could realise a `quiet revolution' using fundamental yet achievable reforms to instill a system-wide perspective among the various UN organizations. The QCPR is seen as the right vehicle to give the UNDS a new sense of purpose as it adapts its business model from aid to sustainable development. It recommends that Member States upgrade the QCPR to a system-wide strategy that links the system-wide what to the how and the means – similar to a corporate strategy in the business world.
Keywords: 330